Microencapsulated paraffin as a tribological additive for advanced polymeric coatings - Reza Gheisari; Mariela Vazquez; Vasilis Tsigkis; Ali Erdemir; Karen L. Wooley; Andreas A. Polycarpou (Friction)
Abstract Numerous tribological applications, wherein the use of liquid lubricants is infeasible, require adequate dry lubrication. Despite the use of polymers as an effective solution for dry sliding tribological applications, their poor wear resistance prevents the utilization in harsh industrial environment. Different methods are typically implemented to tackle the poor wear performance of polymers, however sacrificing some of their mechanical/tribological properties. Herein, we discussed the introduction of a novel additive, namely microencapsulated phase change material (MPCM) into an advanced polymeric coating. Specifically, paraffin was encapsulated into melamine-based resin, and the capsules were dispersed in an aromatic thermosetting co-polyester (ATSP) coating. We found that the MPCM-filled composite exhibited a unique tribological behavior, manifested as “zero wear”, and a super-low coefficient of friction (COF) of 0.05. The developed composite outperformed the state-of-the-art polytetrafluoroethylene (PTFE)-filled coatings, under the experimental conditions examined herein.